Efectividad de las prácticas seguras de enfermería en la atención al paciente pediátrico hospitalizado. - Pinargote Soria, Cinthia Micaela (2024)
The effectiveness of safe practices in the care of hospitalized pediatric patients refers to the effectiveness and efficiency in relation to the purpose of the study and the results that are desired to be obtained through the use of resources that direct care for children and shorten their stay. hospital, therefore, the present bibliographic review aims to analyze the effectiveness of safe nursing practices in the care of hospitalized pediatric patients, through the systematization of information in reliable sources. Documentary and descriptive methodology was used by searching for information in scientific databases, obtaining 59 articles that responded to the research objective. The most important topics are described such as safe practices, adverse events, most frequent complications and effectiveness of their application, finally strategies are proposed aimed at health institutions, nursing staff and main caregivers with the purpose of reducing events caused by poor medical practice. To conclude, the need to apply actions such as the implementation of healthy spaces, education for parents and professionals and the use of models of care for pediatric patients related to safe practices is highlighted so that the quality of care is improved and the quality of care is reestablished. children's health.